2023
DOI: 10.1155/2023/6536768
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Detection of Road Traffic Accident Severity via Data Mining Techniques: Case Study Addis Ababa, Ethiopia

Demeke Endalie,
Wondmagegn Taye Abebe

Abstract: Around the world, road traffic accidents are the leading cause of serious injuries and deaths. Ethiopia is one of the countries that suffer the most from traffic accidents. Every government in every country wants to keep its citizens safe from accidents. To keep people safe from accidents, it is necessary to conduct a detailed analysis of the factors that contribute to high-severity accidents and deaths. As a result, we developed a data mining algorithm-based road traffic accident severity analysis for the Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The traffic accident dataset for this research is drawn from all officially police-reported traffic accidents in Hanoi city over three years (2015−2017) (1132 accidents). Several previous studies have demonstrated that analyzing traffic accident data collected over a threeyear period is appropriate [11,[26][27]. This dataset includes the majority of traffic accidents, which are typically not resolved by the parties involved, involving serious injury or death and reported by the police, instead of encompassing all accidents that happened.…”
Section: Data Collectionmentioning
confidence: 99%
“…The traffic accident dataset for this research is drawn from all officially police-reported traffic accidents in Hanoi city over three years (2015−2017) (1132 accidents). Several previous studies have demonstrated that analyzing traffic accident data collected over a threeyear period is appropriate [11,[26][27]. This dataset includes the majority of traffic accidents, which are typically not resolved by the parties involved, involving serious injury or death and reported by the police, instead of encompassing all accidents that happened.…”
Section: Data Collectionmentioning
confidence: 99%